Lontara Latoa: Study of Da'wah Messages - Mukrim, Ahmad; Amin, Mulyati; Hamiruddin (Jurnal Mercusuar, 2022)
This study discusses Lontara Latoa from the perspective of the Da'wah Message and aims to find out the contents of the da'wah message in Lontara' Latoa and its relationship with Islam. The sub-theme of the research problem; first, an overview of da'wah. Second; an overview of lontara' latoa. Third; da'wah messages and methods of da'wah kajao la liddo in Lontara latoa. This research is library research, namely research that tries to collect data from the literature and make the world of text the main object of its analysis. The data sources for this research are Lontara' Latoa was written by BF Matthes or Lontara' Latoa which has been transliterated and translated by Mattulada. There are also other sources used (secondary data) in this study, namely documents, journals, and relevant scientific papers. The results of this study, based on the search results in Lontara' Latoa conversation between Kajao Laliddo and Arumpone, the authors found 4 things that became the main values of the teachings of Kajao Laliddo's da'wah aimed at rulers and royal officials in carrying out the mandate of the government and power, namely; 1) Honesty (Alempureng); 2) Intellect and Intelligence (Amaccangêng); 3) Persistence (Agêttêngêng); and 4) Family and Compassion (Asseajingêng).